ESTIMATING THE PAYOFF TO SCHOOLING USING THE STANDARD MINCERIAN MODEL - Purnastuti, Losina (Jurnal Economia, 2012)
Abstract: Estimating the Payoff to Schooling using the Standard Mincerian Model. Using data from Indonesia Family Life Survey (IFLS) wave IV, this paper empirically estimates the private rates of return to education in Indonesia. The result from ordinary least-squares estimate shows that one year of schooling increases an individual’s earnings by 5.66 percent. Futhermore, Standard Mincerian Earnings function estimates reveal a gender asymmetry in private economic returns to schooling, with returns to women’s education being substantially and statistically significantly higher than men’s.  Keywords: Return to Schooling, Standard Mincerian Earnings Function Abstrak: Mengestimasi Hasil Investasi Pendidikan Menggunakan Model Mincerian Standar. Menggunakan data Indonesia Family Life Survey (IFLS) IV, artikel ini secara empiris mengestimasi “rates of return” investasi pendidikan di Indonesia. Hasil dari estimasi dengan menggunakan pendekatan OLS menunjukkan bahwa setiap tambahan satu tahun sekolah akan meningkatkan pendapatan individu sebesar 5.66 persen. Estimasi fungsi pendapatan Standard Mincerian mengindikasikan perbedaan “return to schooling” antara perempuan dan laki-laki. “return to schooling” perempuan lebih tinggi dari pada “return to schooling” laki-laki. Kata Kunci: Kembalian Investasi Pendidikan, Fungsi Pendapatan Standar Mincerian